Metode Latihan Ladder Drill Terhadap Peningkatan Kelincahan Pemain Tenis Lapangan - andria, yogi; Igoresky, Andre; Dinata, Windo Wiria; Yendrizal, Yendrizal (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2023)
There are many elements that need to be improved besides the basic techniques in playing tennis. One of the elements that need to be trained is agility and speed. When practicing agility and speed it is very rarely given by trainers in practice. In fact, agility is also necessary and much needed when playing to face opponents who have better quality. The purpose of this study was to determine the effect of the ladder drill training method on increasing the agility of tennis players. The research method used is quasy experiment. The test instrument used is the Illinois Agility Test. The results showed that there was an effect of ladder drill training on agility with an average score of 17.44 in the pretest, and after being given treatment the average score was 16.34 in the posttest. In the results of the pretest and posttest there is a decrease in the average score, this means that there is a significant effect because the final agility test uses less time.